A ‘Turn-on’ Fluorescence Glycosyl Dithiocarbamate Probe for Selective Fluoride Sensing in Aqueous Medium - Das, Rituparna; Mishra, Bedangshu; Mukhopadhyay, Balaram (Synlett, 2018)
A glycosyl dithiocarbamate derivative is developed as a ‘turn on’ fluorescent sensor for fluorides in aqueous medium. The probe is prepared through a simple chemical strategy reported earlier from our group. The virtually nonfluorescent probe showed significant enhancement of fluorescence upon interaction with fluorides in aqueous solution. It was seen to be selective to fluorides too as the interactions with various other anions resulted in very low increase in fluorescence. The simple preparation and unique interaction of the dithiocarbamato derivative with fluorides in aqueous solution promise the development of a novel turn-on probe for the detection of fluorides.
Keywords: carbohydrate; dithiocarbamate; fluoride sensing; multivalency; turn-on probe